A política de socialização da produção científica do Programa de Pós-graduação em Educação da UFC no período de 1997 a 2011 - Amaral, Maria Gerlaine Belchior (2012)
The essence of this investigation is the socialization of the findings of the research carried by the graduate school in pedagogic field. Despite the scientific and technological advances that we see nowadays, the knowledge produced by the university continues restricted to more privileged circles of our society. Realizing this issue took us to put this investigation into practice. Ultimately, it has the goal to analyze the policies of socialization of scientific production, concerning its applicability to public schools, of the UFC Graduate Program in Education, from 1997 to 2011. This thesis asked if the researches developed by the Program were being socialized among active teachers of basic education. The paper is characterized as a case study, its locus being the university itself and the Program previously mentioned. The data obtained here derived from internal documents, the other data, the one concerned with the policies of socialization, were collected through the use of semi-structured interviews. Nine subjects participated, including four, current and former, Program coordinators and other five coordinators of research lines. The analysis was based on the principles of qualitative approach. Initially, a bibliographical research was conducted, making use of three different sources, as follows: dissertations and thesis defended throughout the Program, books and articles directly related to the theme and web search. This study allowed us to conclude that the UFC Graduate Program in Education carried out researches that bring contributions to the public school. As to the policies of socialization of scientific production, it is perceived that it meets its target audience within the walls of academia. However its reach towards public school teachers needs to be reconsidered. Solid actions are required in order that the knowledge derived from academic research can reach the public school.